Artificiell insemination av får - Falk, Alexander (SLU/Dept. of Animal Breeding and Genetics (until 231231), 2010)
Abstract The purpose of this bachelor thesis is to describe the use of artificial insemination (AI) in sheep and discuss the possibilities for AI in Sweden. Male and female fertility, heat detection, semen handling and insemination techniques in sheep are described. Advantages and disadvantages of AI are discussed. In order to achieve genetic progress it is important with well planned and implemented breeding programs. The Swedish Sheep Recording Scheme and computer software from Elitlamm are the basis for sheep breeding in Sweden. Natural mating of ewes are most common and the use of AI is limited. However, there is an increasing interest for use of AI for importation of genetic material and for storage of semen from endangered breeds. In Norway the use of AI has increased in recent years. Two different methods, cervical and vaginal insemination, are used. When using AI it is advantageous if all ewes in the herd are in heat at the same time. Oestrus synchronization can be implemented by means of synthetic hormones or with use of so-called teaser rams. The technique that works best and is recommended in Norway is vaginal insemination. This technique, together with ram synchronized heat is good practice also in Swedish sheep breeding.